Born to run a hidden tribe, superathletes, and the greatest race the world has never seen - McDougall, Christopher 1962- (Vintage Books, 2011)
McDougall reveals the secrets of the world's greatest distance runners--the Tarahumara Indians of Copper Canyon, Mexico--and how he trained for the challenge of a lifetime: a fifty-mile race through the heart of Tarahumara country pitting the tribe against an odd band of super-athletic Americans.